What happens when the nuclear species is absent? Observations of mixedspecies bird flocks in the Hiyare Forest Reserve, Galle, Sri Lanka - Perera, P. L. M. M.; Kotagama, S.W.; Goodale, E.; Kathriarachchi, Hashendra (My University, 2016)
Mixed-species flocks play a prominent role in the social organisation of birds, especially in the tropics (Greenberg 2000, Sridhar et al. 2009) and it has long been observed that some ‘nuclear’ species play essential roles in the formation, maintenance and leadership of mixed-species flocks (Moynihan 1962, Goodale & Beauchamp 2010). Several authors have suggested that when nuclear species are absent, flocks may break up, and this might make flocking species vulnerable to human disturbance (Maldonado-Coelho & Marini 2004, Sridhar & Sankar 2008, Zhang et al. 2013). This could be a particularly interesting example of why non-trophic species interactions should be taken into consideration when devising strategies for conservation (Valiente-Banuet et al. 2015). Here we report on flocks that persist in the absence of a typical nuclear species. In the lowlands of the wet zone of Sri Lanka, Orangebilled Babbler Turdoides rufescens demonstrates all the characteristics of a nuclear species: it is noisy and active, highly gregarious and leads most flocks (Kotagama & Goodale 2004, Jayarathna et al. 2013). A secondary nuclear species might be the Greater Racket-tailed Drongo Dicrurus paradiseus lophorhinus; this taxon—considered by some authorities to be an endemic monotypic species, the Sri Lanka Crested Drongo Dicrurus lophorhinus—makes loud alarm calls (Goodale & Kotagama 2005a) and is as attractive to other species as babblers in playback experiments (Goodale & Kotagama 2005b). However, it is not gregarious and does not facilitate the foraging of other birds, being a sallying species, and one that can also be aggressive and kleptoparasitic (Satischandra et al. 2007). At the Hiyare Forest Reserve study site there are no Orange-billed Babblers, but the Sri Lanka Crested Drongo is present.